Derivações antropogênicas no padrão fitofisionômico do Parque Nacional Serra de Itabaiana - Sergipe - Melo, Bartira Alves de (2022)
The Serra de Itabaiana National Park (PARNASI) is an example of a heterogeneous landscape modeled by both geological and anthropic agents. Situated in a transition area of the Atlantic forest domain with the caatinga, the park is occupied in its largest area by mountain ranges of the Sergipe fold (Meso / Neoproterozoico) (MMA / ICMBIO, 2016). This configuration associated with land use for activities farming and mining witness the modeling of the current landscape. Although the morphostructures of the mountains that make up the park indicate similarities, its phytophysiognomy does not testify to this genetic link. It is believed that, among other factors, the phytophysiognomic pattern expected for the mountains can be influenced by the dynamics of use and occupation of the park and its surroundings. Thus, its general objective is to establish phytophysiognomic patterns through changes between the core and ecotonal areas of the Serra de Itabaiana National Park. The research will be summarized in the quantitative method, which is characterized by the uniqueness of the form of collection and treatment and data. The theoretical-methodological basis is centered on the geosystemic conception of the landscape, due to its integrative and hierarchical character. The methodology will be adapted from the works of Lucas Cavalcanti (2016/2018), where in these works there is a detailed application of the cartographic modeling of the types of geosystems. Thus, the research will follow four steps of procedures: Determination of the limits of the Sites; Determination of State limits; Description of biophysical and land use attributes in the plots; Production schematic profile of topographic profiles. After the conclusion of the research, it is hoped to corroborate the hypothesis of the interference of the forms of land use in PARNASI to play a decisive role in altering the phytophysiognomic patterns of the area, pointing out management measures to minimize or reverse, in the medium and long terms, trend.